TYPES OF GRAMMATICAL ERRORS IN THE ESSAYS WRITTEN BY FOURTH-SEMESTER STUDENTS OF ENGLISH DEPARTMENT, PETRA CHRISTIAN UNIVERSITY - P. E. Limengka; Esther Kuntjara (Kata Kita: Journal of Language, Literature, and Teaching, 2013)
This study deals with errors which include tenses (verb forms), number agreement, and active-passive voice, word order, and word formation on students’ essays.The purpose of this study is to find out the types of errors committed by the students in Written 4 class based on five categories which are addition, omission, misformation, misordering  and blends. The writer found that the most frequent error is misformation, especially the misformation of verbs and nouns. In conclusion, the students committed misformation, misordering, addition, omission, and blends errors; and misformation is the most commonly committed error which is found in their essays.